Effect of Al, Ti and C additions on Widmanstätten microstructures and mechanical properties of cast Al0.6CoCrFeNi compositionally complex alloys. (15th December 2019) - Asabre, A.; Kostka, A.; Stryzhyboroda, O.; Pfetzing-Micklich, J.; Hecht, U.; Laplanche, G.
Abstract: The cast microstructure of the Al0.6 CoCrFeNi compositionally complex alloy was successfully refined with small additions of Al, Ti and C and its mechanical properties were optimized. In the as-cast state, this alloy has a Widmanstätten microstructure with coarse grains (∼110 μm) of a strong BCC/B2 matrix and soft FCC plates (∼65 vol.%) with large widths (∼1.3 μm). The addition of 0.25 at.% C to Al0.6 CoCrFeNi stabilizes the FCC phase and favors the formation of a coarse dendritic microstructure making this alloy unsuitable for structural applications. In contrast, alloying of either 3 at.% Al, Ti, or 3% Ti and 0.25% C to Al0.6 CoCrFeNi refined its Widmanstätten microstructure, i.e. the thickness of the FCC plates and/or the size of the prior BCC/B2 grains were significantly reduced. As a result of these microstructural changes, Al and Ti containing alloys show an outstanding strength (twice higher than that of Al0.6 CoCrFeNi) and ductilities ≤5% at 20 °C. These properties are retained at 400 °C but at 700 °C, the strength and ductility of almost all alloys decrease. However, Ti containing alloys exhibit much larger ductilities (∼50%) at 700 °C due to their high density of grain boundaries which accommodate plastic deformation through grain boundary sliding. Graphical abstract: Unlabelled Image Highlights: Effect of Ti, Al and C additions on microstructure and properties of Al0.6 CoCrFeNi alloy.   The additions of Ti or Ti+C allow to refine the cast microstructure of Al0.6 CoCrFeNi.  This microstructural refinement results in superior mechanical properties. At 700°C, the alloys strongly soften and become more brittle except for those with Ti. These alloys exhibit an excellent ductility due to grain boundary sliding.